MAKNA WANITA JAWA PADA SAMPUL TABLOID WANITA INDONESIA (Analisis Semiotika Rolland Barthes Mengenai Susi Pudjiastuti Pada Sampul Tabloid Wanita Indonesia Edisi 6-12 November 2014) - Gusti Santi Nandra; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Denotation conotation meaning, myth of javanese woman in 6th on 12 november magazine cover of Wanita Indonesia purpose in to know about meaning and analizing of semiotics Rolland Barthes on Susi Pudjiastuti an minister of marine and fisheries.The method that used in this research is qualitative method by semiotics Rolland Barthes as analyse presentation that expressed the symbol that will have to recognize by denotation meaning, conotation and myth. The perpose of this research to describe what happening, in this case, the researcher tried to describe,write, analyse and interpretate the conditions that happened. In tending to use the text data in subjective fom.The results of this research is the meaning of javanese blouse that combined of batik fabric that expressed minister Susi Pudjiastuti as a figure of javanese women who had the leadership. Based on the data, it had corietation in each meaning between the objects that supported the costume of minister Susi Pudjiastuti inauguration the conclution explained the image of minister Susi Pudjiastuti in cover of Wanita Indonesia magazine with good editing by editorial team of Wanita Indonesia magazine, minister Susi Pudjiastuti has shown a beautiful and creative fugure of javanese woman, in cover and articles of Wanita Indonesia magazine.Keyword : Java Women, Tabloid, and Rollad Barthes Thoery